2022
DOI: 10.7717/peerj.14048
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 as a potential biomarker for detecting esophageal carcinoma in Asian populations: a meta-analysis

Abstract: Background MicroRNA-21 (miR-21) is significantly expressed in a variety of cancers and could be used as a tumor biomarker. However, the results are varied, and no studies on the diagnostic usefulness of miR-21 in Asian esophageal cancer (EC) patients have been published. This meta-analysis was aimed at exploring whether miR-21 can be used as a diagnostic marker and assessing its effectiveness. Methods The relevant literature was identified in six main databases: Ovid MEDLINE, PsycINFO, PubMed MEDLINE, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Regarding the prognosis of esophageal cancer, the concurrent disruption of circulating miR-21 and cytotoxic T lymphocytes (CTLs) presents as prospective diagnostic and prognostic markers for esophageal squamous cell carcinoma (ESCC) 21 . Integrative analysis of miRNA-mRNA expression pro les post-esophageal brosis following ESD 22 ,and MicroRNA-21 as a potential biomarker for detecting esophageal carcinoma in Asian populations have been studied in a meta-analysis 23 .The downregulation of lncRNA LINC-PINT is implicated in the recurrence of esophageal squamous cell carcinoma, possibly interacting with miRNA-21 24 . The correlation of plasma miR-21 and miR-93 with the e cacy of radiotherapy and chemotherapy, and prognosis in esophageal squamous cell carcinoma patients, has also been investigated 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prognosis of esophageal cancer, the concurrent disruption of circulating miR-21 and cytotoxic T lymphocytes (CTLs) presents as prospective diagnostic and prognostic markers for esophageal squamous cell carcinoma (ESCC) 21 . Integrative analysis of miRNA-mRNA expression pro les post-esophageal brosis following ESD 22 ,and MicroRNA-21 as a potential biomarker for detecting esophageal carcinoma in Asian populations have been studied in a meta-analysis 23 .The downregulation of lncRNA LINC-PINT is implicated in the recurrence of esophageal squamous cell carcinoma, possibly interacting with miRNA-21 24 . The correlation of plasma miR-21 and miR-93 with the e cacy of radiotherapy and chemotherapy, and prognosis in esophageal squamous cell carcinoma patients, has also been investigated 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Significant overexpression of miRNA-21 in plasma has been reported also in patients with early-stage esophageal cancer. 30 Chen et al showed that plasma microRNA-375 was significantly different between esophageal cancer patients and controls, but found no difference in gender or age. They evaluated the diagnostic value of miRNA-375 37 EC patients and 26 healthy controls.…”
Section: Mirna In Esophageal Cancer Diagnosismentioning
confidence: 99%